UJI EFEK NEFROPROTEKTIF EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) PADA TIKUS JANTAN YANG DIINDUKSI GENTAMISIN - Irma Santi; Aulia Wati; Mauriska Dwiyanti Sjamsuddin (As-Syifaa Jurnal Farmasi, 2022)
Nephroprotective is an attempt to protect the kidneys from damage. The research aimed tc determine the effect of nephroprotective and determine the effective dosage of ethanol extract of Anredera cordifolia (Ten.) Steenis leaf as the nephroprotective. The research used 15 male rats divided into 5 groups. Group 1 (normal) was no treatment; group 2 (negative control) was induced by gentamicin; and groups 3, 4 and 5 (test group) were provided ethanol extract of Anredera cordlfolia Ten.) Steenis leaves sequentially at the doses of 100 mg/KgBW, 150 mg/KgBW and 200 mg/KgBW. The extract was orally given once a day for 8 days; every 1 hour after the treatment, all the test rats were intraperitoneally induced by gentamicin of 80 mg/KgBW except for the normal group. The measurement of creatinine content was conducted on day 1 and 9. Based on the results of the measurement of final creatinine content, the ethanoi exiract of the Madeira-vine leaf obtained had the effect as nephroprotective. From the results of the difference in creatinine content, the analysis was conducted by One-Way ANOVA followed by the LSD test. In conclusion, the ethanol extract of Madeira-vine leaf of the doses of 100 mg/KgBW, 150 mg/KgBW and 200 mg/KgBW had relatively the same nephroprotective effect.